Determinants of Pelvic Floor Disorders among Women Visiting the Gynecology Outpatient Department in Wolkite University Specialized Center, Wolkite, Ethiopia - Ayana Benti Terefe; Tolesa Gemeda Gudeta; Girma Teferi Mengistu; Seboka Abebe Sori (Obstetrics and Gynecology International)
Background. Pelvic floor disorders encompass a broad range of interrelated clinical conditions. Pelvic floor disorders are a common public health concern that affects the lives of millions of adult females. This disorder is expected to be more widespread and probably more severe among women in low-income countries. However, there is limited knowledge about pelvic floor disorders and their determinants among women in Ethiopia. Objective. The purpose of the study was to assess the determinants of pelvic floor disorders among women who visited the gynecology outpatient service at the Wolkite University Specialized Hospital, Wolkite, Ethiopia, in 2021. Methods. A cross-sectional hospital study was conducted on 275 randomly chosen women from June 1 to July 1, 2021. A systematic sampling technique was used when selecting the study subjects. The data were gathered using interviewer administered structured questionnaires. The data collected was entered in version 3.1 of EpiData, and version 23 of Statistical Package for Social Sciences was used for the analysis. The variables with a P-value <0.25 in the bivariate analysis were considered for a subsequently built multivariable model, and factors with P<0.05 in the final model were statistically significant. The results were presented in an adjusted odds ratio with a 95% confidence interval. Result. The prevalence of pelvic floor disorder was reported to be 17.8% with 9.3% of the women experiencing urinary incontinence, 8.9% experiencing pelvic organ prolapse, and 5.9% experiencing anal incontinence. Two hundred thirty-two (85.9%) were currently married, while 110 (40.7%) were housewives. Statistically, a significant association was found between age at first pregnancy (AOR = 5.193; 95% CI = 1.905–14.157), many vaginal deliveries (AOR = 15.858; 95% CI = 5.305–47.400), history of episiotomy (AOR = 7.508 95% CI = 1.556–36.224), and menopause (AOR = 7.665; 95% CI = 2.440–24.078) when analyzed with a multivariate logistic regression model. Conclusion. In this study, age at first pregnancy, number of vaginal births, history of episiotomy, and menopause were independently associated with pelvic floor disorder. Therefore, educating women about the year of their first pregnancy, promoting family planning, and advice on the prevention of routine episiotomy by a health professional is recommended.